2007
DOI: 10.1136/gut.2006.115352
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone prevents visceral hyperalgesia but not colonic permeability increase induced by luminal protease-activated receptor-2 agonist in rats

Abstract: Background: Low-grade inflammation may play a role in the pathogenesis of irritable bowel syndrome (IBS). Although corticosteroids are potent inhibitors of inflammatory processes, only one study with corticosteroids in patients with postinfectious IBS exists, which suggests that prednisolone is not an effective treatment for IBS symptoms. Aim: To evaluate whether dexamethasone treatment prevents protease-activated receptor-2 (PAR-2) activation-induced visceral hyperalgesia and increased permeability in rats, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 41 publications
0
22
2
Order By: Relevance
“…&P \ 0.001, %P \ 0.05, compared with IBS-C patients Dig Dis Sci (2012) 57:58-64 61 IBS patients or subgroups compared with control subjects. It has been reported that PAR2 expression on enterocytes is regulated by luminal serine proteases [22]. In our study, although the mRNA expressions of tryptase and trypsin were higher in IBS patients, PAR2 expression was lacking a significant difference.…”
Section: Discussioncontrasting
confidence: 62%
“…&P \ 0.001, %P \ 0.05, compared with IBS-C patients Dig Dis Sci (2012) 57:58-64 61 IBS patients or subgroups compared with control subjects. It has been reported that PAR2 expression on enterocytes is regulated by luminal serine proteases [22]. In our study, although the mRNA expressions of tryptase and trypsin were higher in IBS patients, PAR2 expression was lacking a significant difference.…”
Section: Discussioncontrasting
confidence: 62%
“…Other factors such as histamine, serotonin, and prostaglandins may also contribute to the increased permeability seen in IBS patients [5], and elevated colonic luminal serine protease activity of IBS-D patients could evoke a PAR-2-mediated colonic epithelial dysfunction as well [3]. This result could partially explain why dexamethasone treatment does not prevent protease-activated receptor-2 (PAR-2) agonist-induced increase in colonic permeability [25].…”
Section: Discussionmentioning
confidence: 95%
“…The A5 antibody is equivalent to the previously described B5 antiserum. A5 has been obtained in exactly the same way as B5, and both have the same specificity (2,31,32). Expression of PAR-2 was visualized using a Cy3-conjugated goat anti-rabbit secondary antibody (1 h, room temperature, 1:250, PA43004; GE Healthcare, Buckinghamshire, UK).…”
Section: Par-2 Expression: Immunofluorescent Staining and Analysismentioning
confidence: 99%